TLR4 abrogates the Th1 immune response through IRF1 and IFN-β to prevent immunopathology during L. infantum infection - Sacramento, Laís Amorim; Benevides, Luciana; Maruyama, Sandra Regina; Tavares, Lucas; Fukutani, Kiyoshi Ferreira; Francozo, Marcela; Sparwasser, Tim; Cunha, Fernando Queiroz; Almeida, Roque Pacheco; da Silva, João Santana; Carregaro, Vanessa (PLoS pathogens, 2020)
A striking feature of human visceral leishmaniasis (VL) is chronic inflammation in the spleen and liver, and VL patients present increased production levels of multiple inflammatory mediators, which contribute to tissue damage and disease severity. Here, we combined an experimental model with the transcriptional profile of human VL to demonstrate that the TLR4-IFN-β pathway regulates the chronic inflammatory process and is associated with the asymptomatic form of the disease. Tlr4-deficient mice harbored fewer parasites in their spleen and liver than wild-type mice. TLR4 deficiency enhanced the Th1 immune response against the parasite, which was correlated with an increased activation of dendritic cells (DCs). Gene expression analyses demonstrated that IRF1 and IFN-β were expressed downstream of TLR4 after infection. Accordingly, IRF1- and IFNAR-deficient mice harbored fewer parasites in the target organs than wild-type mice due to having an increased Th1 immune response. However, the absence of TLR4 or IFNAR increased the serum transaminase levels in infected mice, indicating the presence of liver damage in these animals. In addition, IFN-β limits IFN-γ production by acting directly on Th1 cells. Using RNA sequencing analysis of human samples, we demonstrated that the transcriptional signature for the TLR4 and type I IFN (IFN-I) pathways was positively modulated in asymptomatic subjects compared with VL patients and thus provide direct evidence demonstrating that the TLR4-IFN-I pathway is related to the nondevelopment of the disease. In conclusion, our results demonstrate that the TLR4-IRF1 pathway culminates in IFN-β production as a mechanism for dampening the chronic inflammatory process and preventing immunopathology development.